Peran Pemimpin Gereja Dalam Kepemimpinan Pelayanan Kaum Muda Masa Kini - Heryanto Heryanto (STTI Harvest Semarang, 2020)
Today's youth ministry is a ministry that has very different challenges and struggles than the youth ministry in the previous decade. The need for leaders in the service of young people today is needed so that youth services can be strong. Through a qualitative review of the literature using a practical theological research method that will discuss the role of church leaders in the leadership of youth ministry today. The purpose of this research is expected to open new understanding for church leaders to build and guide young people to become leaders for youth ministry. The benefit of this research is that the presence of young people in the church is well served to grow prospective young leaders who bring glory to the name of the Lord Jesus. Found several things that must be done by church leaders in building and guiding young people to be leaders in youth ministry are: First, as a spiritual guide. Second, as a pilot model followed. Third, the personal example of having the love of Jesus Christ and loving others. Fourth, inspire young people to give dedication to Jesus Christ and Fifth, to encourage spiritual growth and character. Pelayanan kaum muda pada masa kini merupakan pelayanan yang memiliki tantangan dan pergumulan yang amat berbeda dibandingkan pelayanan kaum muda dalam dekade sebelumnya. Kebutuhan terhadap para pemimpin dalam pelayanan kaum muda masa kini sangat dibutuhkan agar pelayanan anak muda dapat menjadi kuat. Melalui kajian kualitatif literatur menggunakan metode penelitian teologi praktika yang akan membahas peran pemimpin gereja dalam kepemimpinan pelayanan kaum muda masa kini. Tujuan penelitian ini diharapkan membuka pengertian baru bagi para pemimpin gereja untuk membangun dan membimbing kaum muda untuk menjadi para pemimpin bagi pelayanan kaum muda. Manfaat penelitian ini adalah agar keberadaan kaum muda di gereja terlayani dengan baik sehingga menumbuhkan calon pemimpin kaum muda yang membawa kemuliaan bagi nama Tuhan Yesus. Didapati beberapa hal yang harus dilakukan para pemimpin gereja dalam membangun dan membimbing para kaum muda menjadi pemimpin dalam pelayanan kaum muda adalah : Pertama, sebagai pembimbing rohani. Kedua, sebagai model percontohan yang diiikuti. Ketiga, contoh pribadi yang memiliki kasih Yesus Kristus dan mengasihi sesama. Keempat, menginspirasi kaum muda dalam memberi dedikasi kepada Yesus Kristus dan kelima, pendorong pertumbuhan rohani dan karakter.